Eurycoma longifolia: Medicinal Plant in the Prevention and Treatment of Male Osteoporosis due to Androgen Deficiency. (15th July 2012) - Mohd Effendy, Nadia; Mohamed, Norazlina; Muhammad, Norliza; Naina Mohamad, Isa; Shuid, Ahmad Nazrun
Abstract : Osteoporosis in elderly men is now becoming an alarming health issue due to its relation with a higher mortality rate compared to osteoporosis in women. Androgen deficiency (hypogonadism) is one of the major factors of male osteoporosis and it can be treated with testosterone replacement therapy (TRT). However, one medicinal plant, Eurycoma longifolia Jack ( EL ), can be used as an alternative treatment to prevent and treat male osteoporosis without causing the side effects associated with TRT. EL exerts proandrogenic effects that enhance testosterone level, as well as stimulate osteoblast proliferation and osteoclast apoptosis. This will maintain bone remodelling activity and reduce bone loss. Phytochemical components of EL may also prevent osteoporosis via its antioxidative property. Hence, EL has the potential as a complementary treatment for male osteoporosis.